2022
DOI: 10.15330/pcss.23.2.261-269
|View full text |Cite
|
Sign up to set email alerts
|

Electron, phonon, optical and thermodynamic properties of CdTe crystal calculated by DFT

Abstract: Electronic and phonon band structure, thermodynamic and optical properties are studied for the CdTe crystal. We calculated the electron and phonon dispersion at high symmetry directions, density of electron and phonon state, temperature dependence feature of Raman spectra, heat capacity, free energy, entropy, enthalpy and Debay temperature estimated with the generalized gradient approximation (GGA). A Perdew–Burke–Ernzerhof functional (PBE) was utilized. To study the optical properties was use a complex dielec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Also, the minimum value, 43.3 GPa, was obtained for Cd0.7Au0.25Te and not much higher (46.3 GPa) for Cd0.7Cu0.25Te. If compared these data with the data obtained from a calculation using the same method for CdTe (45.13 GPa [35]), we can see that the solid-state Cd0.75Cu0.25Te solution shows a much close value.…”
Section: Crystal Structure Of Solid-state Cd075x025te (X= Cu Ag and A...mentioning
confidence: 84%
See 2 more Smart Citations
“…Also, the minimum value, 43.3 GPa, was obtained for Cd0.7Au0.25Te and not much higher (46.3 GPa) for Cd0.7Cu0.25Te. If compared these data with the data obtained from a calculation using the same method for CdTe (45.13 GPa [35]), we can see that the solid-state Cd0.75Cu0.25Te solution shows a much close value.…”
Section: Crystal Structure Of Solid-state Cd075x025te (X= Cu Ag and A...mentioning
confidence: 84%
“…In preview work [35], was reported about electron, phonon, optical and thermodynamic properties of the CdTe crystal. In the present work, the electronic energy spectra of the solid-state Cd0.75X0.25Te (X= Cu, Ag and Au) solutions have been calculated for the first time.…”
Section: Methods Of Calculationmentioning
confidence: 99%
See 1 more Smart Citation